1995
DOI: 10.1557/jmr.1995.2599
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of titanium boride (TiB)2 nanocrystallites by solution-phase processing

Abstract: Nanocrystalline TiB 2 is prepared by reaction of NaBH 4 and TiCU. The initial solution-phase reaction affords an amorphous precursor powder from which 5-100 nm TiB 2 crystallites are obtained upon annealing at 900-1100 °C. Crystallite sizes depend on the annealing temperature and other processing parameters. Crystallite morphology is size dependent; crystallites smaller than 12-15 nm are cuboidal, whereas crystallites larger than 12-15 nm are hexagonal platelets. The procedure affords gram quantities of the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…A number of processes exist for synthesizing TiB 2 powder such as direction reaction of Ti and B, 7 metal-thermal reduction, 8 arc-plasma method 9,10 and gasphase combustion (flame) method. 11 Normally, TiB 2 powder is commercially produced by reduction of titanium oxide with either boron oxide and carbon or an alkali metal and boron oxide. [15][16][17] Among above mentioned processing techniques, the carbothermal reduction process is commercially used by far the cheapest because of inexpensive raw materials and simple process.…”
Section: Introductionmentioning
confidence: 99%
“…A number of processes exist for synthesizing TiB 2 powder such as direction reaction of Ti and B, 7 metal-thermal reduction, 8 arc-plasma method 9,10 and gasphase combustion (flame) method. 11 Normally, TiB 2 powder is commercially produced by reduction of titanium oxide with either boron oxide and carbon or an alkali metal and boron oxide. [15][16][17] Among above mentioned processing techniques, the carbothermal reduction process is commercially used by far the cheapest because of inexpensive raw materials and simple process.…”
Section: Introductionmentioning
confidence: 99%
“…These excellent properties make it a potential material for applications as ballistic armour, coating on cutting tools, cathodes for electro-chemical processing of aluminium (Hall -Heroult process), high-temperature evaporation boats, high-temperature sleeves and as dispersoid in metal or ceramic matrix composites [1,2]. Several methods for the preparation of TiB 2 powders are reported, amongst them, the borothermic reduction of titania, carbothermic reduction of the TiO 2 and B 2 O 3 powder mixture, reduction of titania with boron carbide [2,3], reactions of elemental powders by powder metallurgical route, solution-phase processing route by reaction of NaBH 4 and TiCl 4 [4], gas-phase combustion synthesis process based on the gas-phase Na/TiCl 4 /BCl 3 flame reaction [5] and self-propagating high-temperature synthesis (SHS) technique are noteworthy. In the SHS process, once the combustion reaction is ignited, extremely high temperatures can be achieved within a very short time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various efforts have been made to synthesize TiB 2 at lower temperatures, control morphology or simplify reaction procedures. For example, Gu et al [6] prepared nanocrystalline titanium diboride via a benzene-thermal reaction of metallic sodium with amorphous boron powder and titanium tetrachloride at 400°C; Axelbaum et al [7] reported to synthesize nanometer-sized TiB 2 particles by gas-phase combustion reaction of sodium vapor with TiCl 4 and BCl 3 in a high-temperature flow reactor; Bates et al [8] reported a solution-phase reaction of NaBH 4 and TiCl 4 to produce an amorphous precursor powder, which was then annealed at 900-1100°C to obtain nanocrystalline TiB 2 .…”
mentioning
confidence: 99%